Acupuncture for acute ischemic stroke: A systematic review and meta-analysis of randomized controlled trials - Shanshan Huang; Yuting Wang; Yifan Wu; Puchen Huang; Yu Dong; Qiao Zhang; Mengjiao Zhao; Jingchun Zeng; Liming Lu; Xinxia Liu (Integrative Medicine Research)
Background: Stroke is the main cause of death and disability worldwide. There are divergent views regarding the effects of acupuncture in managing acute ischemic stroke (AIS). The purpose of this study was to assess the safety and effectiveness of acupuncture for acute ischemic stroke. Methods: We conducted a comprehensive search across the PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang, and SinoMed databases from their inception until October 3, 2023. Two reviewers screened eligible randomized controlled trials (RCTs) according to criteria and extracted data using a pre-established form. Cochrane tool was used for risk of bias assessment, and Revman 5.3 was used for subsequent meta-analysis. The GRADE tool will be used to assess the quality of evidence. Results: Thirty-one RCTs were included, involving 3604 patients. Meta-analysis showed that compared with conventional treatments (CTs), acupuncture combined with CTs could improve in National Institutes of Health Stroke Scale (NIHSS) and Efficiency (MD:1.70, 95 %CI [-2.27, -1.14], P < 0.00001;RR: 1.21, 95 %CI [1.12, 1.31], P < 0.00001,);On the Chinese Stroke Scale (CSS) and effectiveness based on CSS, acupuncture showed positive effects (MD:4.33, 95 %CI [-5.67, -2.98], P < 0.00001; RR: 1.26, 95 %CI [1.13, 1.41], P < 0.0001). Furthermore, ADL, Fugl-Meyer Assessment Scale (FMA), prognosis analyses also showed the effectiveness of acupuncture. (SMD: 0.98, 95 % CI [0.64, 1.31], P < 0.00001; MD: 16.46, 95 %CI [12.56, 20.35], P < 0.00001; RR: 0.38, 95 %CI [0.16, 0.89], P = 0.03). However, the certainty of evidence was low. Conclusion: According to current evidence, Acupuncture may be effective and safe for AIS. The future still needs high-quality evidence to support this conclusion. Protocol registration: PROSPERO (CRD42023464998).